Troxipide in the Management of Gastritis: A Randomized Comparative Trial in General Practice - Bhupesh Dewan; Aarthi Balasubramanian (Gastroenterology Research and Practice)
Background. A trial of empirical acid-suppressive therapy is the usual practice for most patients with symptoms of gastritis in primary care. Aim. To assess the relative efficacy of Troxipide and Ranitidine in patients with endoscopic gastritis over a four-week period. Methods. In all, 142 patients were randomized to Troxipide (100 mg tid) or Ranitidine (150 mg bid) for a period of four weeks. The severity of the signs of endoscopic gastritis at baseline and week 4 using a four-point scale and the subjective symptom severity at baseline and week 2 & week 4 using a Visual analog scale (VAS) were documented. Results. Troxipide was found to be superior to Ranitidine for both, the complete resolution and improvement of endoscopic gastritis. Higher proportion of patients showed complete healing of erosions (88.14%), oozing (96.77%), and edema (93.88%) with Troxipide as compared to Ranitidine (𝑃<.01). Patients receiving Troxipide also showed a greater improvement in the VAS scores for abdominal pain, bloating, and heartburn (𝑃<.01). Both the drugs were found to be well tolerated. Conclusion. In patients with endoscopic gastritis, Troxipide, with its superior rate of improvement, resolution of signs, and subjective clinical symptoms, can be considered as an alternative to the commonly used antisecretory agents.